Effect of Area‐Level Socioeconomic Deprivation on Risk of Cognitive Dysfunction in Older Adults. Issue 7 (12th February 2018) - McCann, Adrian; McNulty, Helene; Rigby, Jan; Hughes, Catherine F.; Hoey, Leane; Molloy, Anne M.; Cunningham, Conal J.; Casey, Miriam C.; Tracey, Fergal; O'Kane, Maurice J.; McCarroll, Kevin; Ward, Mary; et al.
Abstract : OBJECTIVES: To investigate the relationship between area‐level deprivation and risk of cognitive dysfunction. DESIGN: Cross‐sectional analysis. SETTING: The Trinity, Ulster, and Department of Agriculture (TUDA) study from 2008 to 2012. PARTICIPANTS: Community‐dwelling adults aged 74.0 ± 8.3 without dementia (N = 5, 186; 67% female). MEASUREMENTS: Adopting a cross‐jurisdictional approach, geo‐referenced address‐based information was used to map and link participants to official socioeconomic indicators of deprivation within the United Kingdom and the Republic of Ireland. Participants were assigned an individual deprivation score related to the smallest administrative area in which they lived. These scores were categorized into comparable quintiles, that were then used to integrate the datasets from both countries. Cognitive health was assessed using the Mini‐Mental State Examination (MMSE); cognitive dysfunction was defined as a MMSE score of 24 or less. RESULTS: Approximately one‐quarter of the cohort resided within the most‐deprived districts in both countries. Greater area‐level deprivation was associated with significantly lower MMSE scores; fewer years of formal education; greater anxiety, depression, smoking and alcohol use, and obesity; and more adverse outcomes, including higher blood pressure and diabetes risk. After adjustment for relevant covariates, area deprivation was associated with significantly higher risk of cognitive dysfunction (odds ratio = 1.40, 95% confidence interval = 1.05–1.87, P  = .02, for most vs least deprived). CONCLUSION: This analysis combining data from two health systems shows that area deprivation is an independent risk factor for cognitive dysfunction in older adults. Adults living in areas of greatest socioeconomic deprivation may benefit from targeted strategies aimed at improving modifiable risk factors for dementia. Further cross‐national analysis investigating the impact of area‐ level deprivation is needed to address socioeconomic disparities and shape future policy to improve health outcomes in older adults.© 2018 American Geriatrics Society and Wiley Periodicals, Inc. Abstract : See related editorial by Soo Borson .